2013
DOI: 10.1186/1471-2296-14-110
|View full text |Cite
|
Sign up to set email alerts
|

Practice assistants in primary care in Germany – associations with organizational attributes on job satisfaction

Abstract: BackgroundJob satisfaction and organizational attributes in primary care teams are important issues as they affect clinical outcomes and the quality of health care provided. As practice assistants are an integral part of these teams it is important to gain insight into their views on job satisfaction and organizational attributes. The aim of this study was to evaluate the job satisfaction of practice assistants and the organizational attributes within their general practices in Germany and to explore the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Unfortunately, there is no official database available to compare our sample with the whole population of primary care practice assistants in Germany. However, the distributions for gender, age, working hours and duration of employment in a practice obtained from our study through an online survey were comparable to those observed in other studies (Gavartina et al, ; Goetz et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Unfortunately, there is no official database available to compare our sample with the whole population of primary care practice assistants in Germany. However, the distributions for gender, age, working hours and duration of employment in a practice obtained from our study through an online survey were comparable to those observed in other studies (Gavartina et al, ; Goetz et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…The distribution was positively skewed with the exception of the “income” variable, which was right‐skewed due to the practice assistants’ low satisfaction. Other studies have also shown that non‐medical personnel report low satisfaction with income (Gavartina et al, ; Goetz et al, ). The relatively low factor loading of the “billable services” variable can be explained because, in contrast to other variables, billing services may not directly affect practice assistants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional to a quality‐management system is the description of organisational attributes, such as with SOADC, which seems important for achieving good quality of care. However, to our knowledge there is currently only one study that has used the instrument in primary care and the findings showed that job satisfaction is associated with ‘communication’, ‘decision making’ and ‘stress’. Further research in the field of organisational attributes using SOAPC or SOADC is needed, not only for primary care but also for dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Job satisfaction consists of intrinsic and extrinsic factors, such as physical working condition, recognition of work, satisfaction with colleagues, remuneration and working hours. Moreover, it was shown that these different aspects are associated with different organisational attributes, such as 'communication', 'decision-making' and 'stress' 17 . The internal consistency of the job satisfaction scale was 0.873.…”
Section: Methodsmentioning
confidence: 99%